Prevalence of dental anomalies and enamel hypoplasia in primary dentition among preschool children of West Godavari District, Andhra Pradesh -A cross - sectional study - Suzan Sahana; Srikanth Koya; Aron Arun Kumar Vasa; Kotha Ravichandra Sekhar; Sayesh Vemuri; V Sudhakar (Wolters Kluwer Medknow Publications, 2013)
Background: It is axiomatic that Pediatric dental anomalies and enamel hypoplasia (E.H) are routinely encountered in primary dentition and early detection and prudent management of the condition facilitates normal occlusal development. Objectives: To determine the prevalence of various dental anomalies and enamel hypoplasia in preschool children between two to six years of age. Materials & Method: A total of 1898 children, between two to six years were randomly selected and screened for dental anomalies and enamel hypoplasia The chi square test was used to analyze the data statistically. Results: The overall prevalence rate of dental anomalies and enamel hypoplasia in this study was 0.63% and 8.95% respectively. Double teeth were the most frequently reported dental anomaly while supernumerary teeth were least reported. None of them reported with hypodontia.